2022
DOI: 10.1002/hbm.26055
|View full text |Cite
|
Sign up to set email alerts
|

Functional brain networks underlying the interaction between central and peripheral processes involved in Chinese handwriting in children and adults

Abstract: The neural mechanisms that support handwriting, an important mode of human communication, are thought to be controlled by a central process (responsible for spelling) and a peripheral process (responsible for motor output). However, the relationship between central and peripheral processes has been debated. Using functional magnetic resonance imaging, this study examined the neural mechanisms underlying this relationship in Chinese handwriting in 36 children (mean age = 10.40 years) and 56 adults (mean age = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 75 publications
(121 reference statements)
0
0
0
Order By: Relevance
“…One possible reason for these associations could be due to good penmanship requires lots of handwriting practices, which is highly interactive with the linguistic processes (e.g., orthographic lexicon, semantic system, phonological lexicon and so on). For instance, previous studies on Chinese handwriting have been shown that lexical variables, such as character frequency and regularity etc, modulating the central and peripheral processes of handwriting (Wang et al, 2020;Huang, Zhou, et al, 2021;Huang, Lin, et al, 2021;neuroimaging studies: Yang et al, 2022;Li et al, 2023). Therefore, the end product of handwriting: penmanship, may inherit crucial details of individuals' language competence, However, there are currently not many automatic tools for penmanship assessment.…”
Section: Assessing Handwritingmentioning
confidence: 99%
“…One possible reason for these associations could be due to good penmanship requires lots of handwriting practices, which is highly interactive with the linguistic processes (e.g., orthographic lexicon, semantic system, phonological lexicon and so on). For instance, previous studies on Chinese handwriting have been shown that lexical variables, such as character frequency and regularity etc, modulating the central and peripheral processes of handwriting (Wang et al, 2020;Huang, Zhou, et al, 2021;Huang, Lin, et al, 2021;neuroimaging studies: Yang et al, 2022;Li et al, 2023). Therefore, the end product of handwriting: penmanship, may inherit crucial details of individuals' language competence, However, there are currently not many automatic tools for penmanship assessment.…”
Section: Assessing Handwritingmentioning
confidence: 99%